Phenol formaldehyde as binder for rubberwood oriented strand board (OSB) / Suffian Misran, Rafeadah Rusli and Rahim Sudin - Misran, Suffian; Rusli, Rafeadah; Sudin, Rahim (2006)
Phenol formaldehyde (PF) is a thermoset resin that has been widely used as binder for wood composite products. Since the products differed in material and applications, the resin is usually varied in term of physical and chemical properties to tailor with the requirements as to give good properties to the products. The preparation method of PF resin was one of the factors affecting its properties. This study was carried out to look into the effect of preparation method on the properties of PF resin and oriented strand board (OSB) made from rubberwood. Two alkaline resins were synthesised in the laboratory. They were similar in chemical molar ratios but used slightly different preparation method. The viscosity, solids content, alkalinity, specific gravity, pH and gel time of the resins were determined. The resins then mixed with rubberwood flakes. Boards at 650 kg/m3 density had been produced with resin loading of 3, 5 and 7% of the board weight. The furnish boards were tested according to European Standards to determine the modulus of rupture, modulus of elasticity, internal bond and thickness swelling. The results showed that the resins differed in the viscosity and gel time. Boards produced with the resins have significant different in the physical and mechanical properties.